How external interests enter the European Commission: mechanisms at play in legislative position formation - Hartlapp, Miriam; Metz, Julia; Rauh, Christian (2010)
Abstract: "The European Commission, Europe's central supranational bureaucracy, is often depicted as a playground for external interests. The scholarly literature offers a range of sensible explanations how the Commission position is bound by national, organised societal, or party political interests. Despite substantial contributions, the empirical approach supporting such arguments often focuses on the mere comparison between a particular external interest and the legislative outcome. In this paper, we aim to add a more process-based, mechanismic perspective by empirically focussing the question how certain external interest found their way into a Commission position as captured by a legislative proposal. Against the background of a larger research project which analyses 48 position formation processes in the Commission on the basis of 133 in-depth interviews with participating officials, this paper presents mechanisms linking external interest to the final Commission position and that are